What is nursing professionalism? a concept analysis - Huili Cao; Yejun Song; Yanming Wu; Yifei Du; Xingyue He; Yangjie Chen; Qiaohong Wang; Hui Yang (BMC, 2023)
Abstract Background Nursing professionalism plays an important role in clinical nursing. However, a clear conceptual understanding of nursing professionalism is lacking. Method Walker and Avant's strategy was used to analyse the concept of nursing professionalism. We searched electronic databases, including PubMed, Scopus, and CINAHL, for studies published from 1965 to 2021. Quantitative or qualitative studies published in English that focused on nursing professionalism were included in the study. Results The three attributes of nursing professionalism are multidimensional, dynamic, and culture oriented. Based on the analysis, nursing professionalism is defined as providing individuals care based on the principles of professionalism, caring, and altruism. Conclusions This study offers a theoretical definition and conceptual model of nursing professionalism that may be applied to develop standardized assessment tools or nursing professionalism training programs.